Establishing Community-Based Mental Health Services: The Role of Occupational Therapists and Key Challenges - Špela Mihevc BSc OT, MSc; Katarina Galof BSc OT, PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Slovenia is following the World Health Organization’s guidelines for the development of community-based services by establishing interdisciplinary teams in mental health centres. The literature indicates that occupational therapy in these teams actively contributes to promoting engagement and participation in meaningful occupations that support well-being in the community. The purpose of this study is to highlight the early stages of the development of these teams and the role of occupational therapy in this process. This qualitative study explored occupational therapists’ perspectives on the challenges and their role in practice in community-based mental health (CbMH) centres. Three occupational therapists participated in the first focus group and 4 in the second. Two occupational therapists participated in semi-structured interviews. In total, 9 occupational therapists from 14 menthal health centres participated in the study. The results underline the importance of developing CbMH centres that provide services within clients’ living and working environments. These centres enable occupational therapists to practice in community settings, presenting both opportunities and challenges in integrating occupational therapy into the deinstitutionalisation process. Data analysis identified 3 key thematic areas: the role of the interdisciplinary mental health team in CbMH centres challenges faced by occupational therapists within these teams, and the development of an occupational therapy service model. This study highlights the need to expand CbMH centres across Slovenia and secure additional funding to strengthen existing teams. Key steps for better integration of occupational therapists include advocating for financial recognition, adapting successful international programmes, improving education and training and ensuring the participation of occupational therapists in all interdisciplinary mental health teams.